Ultracompact and high-efficiency liquid-crystal-on-silicon light engines for augmented reality glasses - Zhenyi Luo; Yuqiang Ding; Fenglin Peng; Guohua Wei; Yun Wang; Shin-Tson Wu (Opto-Electronic Advances)
In lightweight augmented reality (AR) glasses, the light engines must be very compact while keeping a high optical efficiency to enable longtime comfortable wearing and high ambient contrast ratio. “Liquid-crystal-on-silicon (LCoS) or micro-LED, who wins?” is recently a heated debate question. Conventional LCoS system is facing tremendous challenges due to its bulky illumination systems; it often incorporates a bulky polarizing beam splitter (PBS) cube. To minimize the formfactor of an LCoS system, here we demonstrate an ultracompact illumination system consisting of an in-coupling prism, and a light guide plate with multiple parallelepiped extraction prisms. The overall module volume including the illumination optics and an LCoS panel (4.4-μm pixel pitch and 1024x1024 resolution elements), but excluding the projection optics, is merely 0.25 cc (cm3). Yet, our system exhibits an excellent illuminance uniformity and an impressive optical efficiency (36%–41% for a polarized input light). Such an ultracompact and high-efficiency LCoS illumination system is expected to revolutionize the next-generation AR glasses.